Proposal of a model for evaluating satisfaction with the physical work environment in educational institutions - Tusset, Rodrigo; Borges Vieira, Guilherme Bergmann; Lazzari, Fernanda; Gonçalves, Roberto Birch (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: Propose a model for evaluating satisfaction with the physical work environment in educational institutions, emphasizing variables such as lighting, ventilation, color, noise, and indoor plants to identify improvements that enhance worker satisfaction. Methodology/approach: Literature review and theoretical-propositional development. The research was based on academic articles that explore the impact of the physical environment on employee satisfaction. Identified variables were grouped and analyzed based on their relevance to the environment of educational institutions. Originality/Relevance: Proposal of a model adaptable to public educational institutions, focusing on variables that affect satisfaction and contributing to management with a tool for improving the physical work environment. Key findings: The physical work environment directly affects employee satisfaction. Improvements in lighting, ventilation, color, noise, and indoor plants can increase worker satisfaction, well-being, and productivity. The proposed model provides a foundation for future interventions and adjustments in the physical environment, adapting to the specific needs of each institution. Theoretical/methodological contributions: The study provides a conceptual basis for creating a more favorable physical environment in public educational institutions, contributing to the debate on job satisfaction. It is recommended to apply a quantitative approach using questionnaires in future research to validate the model.